K-Beauty Craze in Indonesia: A Study of Consumer Purchase Intentions - Laulita, Nasar Buntu; Clorina, Jesslyn (Politeknik Negeri Padang, 2023)
This study investigates how brand ambassadors, digital marketing and brand image influences consumer purchase intention for beauty products in South Korea with brand trust as a mediating variable. This research involved 230 people from Indonesia who had bought beauty products from South Korea in which purposive sampling method is applied in the collection of relevant data. Partial Least Square (PLS) data analysis method is applied which is then processed in the SmartPLS software. It is found that brand ambassadors and digital marketing does have a positive and significant effect on brand trust. On the other hand, brand ambassador, brand image and brand trust have a significant positive effect on purchase intention as well. The mediation results show that brand trust as a mediator can mediate significantly and positively between brand ambassadors on purchase intention, which means that through well-known brand ambassadors with a good reputation, they can help company brands in maintaining consumer trust in brands and encourage interest in buying products indirectly.